Synthesis of the Anti-Melanogenic Glycerol Fatty Acid Ester Isolated from the Tuber-Barks of Colocasia antiquorum var. esculenta - Zhu, Shijun; Wu, Yikang (Synlett, 2014)
(2′S)-1-O-9-Oxo-(10E,12E)-octadecadienoyl glycerol, a natural anti-melanogenic monoglyceride, is synthesized for the first time. The chiral pool based route employed not only confirms the absolute configuration, but also illustrates the first synthetic entry to the (E,E)-diene keto acid, which is another molecule of biological importance. The confusion caused by the misinterpreted 1H NMR spectroscopic data for the (E,E)-diene motif in the literature is discussed. The first unequivocal piece of evidence for the assigned (12E) configuration is also presented.
Keywords: diols; acylation; glycerolipids; rearrangement; natural products